A Method for the Isolation of Thymoquinone from Black Caraway Seed Oil (Nigella sativa L.) - A. K. Whaley; Y. V. Burtseva; E. V. Kuldyrkaeva; A. S. Novosad; N. L. Babak; E. V. Zhokhova; A. O. Whaley; M. Yu. Goncharov; I. I. Terninko; G. P. Yakovlev (Разработка и регистрация лекарственных средств, 2023)
Introduction. Thymoquinone (2-Isopropyl-5-methyl-1,4-benzoquinone) is an organic compound of plant origin, which is formed as a result of the oxidation of thymohydroquinone. Thymoquinone is a component of the essential oil of black caraway seeds (Nigella sativa L.) and is known to possess a significant spectrum of pharmacological activity. Due to the lipophilicity of thymoquinone and its ability to accumulate in oils, we proposed a method to isolate thymoquinone from the fatty oil of caraway seeds in order to assess its selective accumulation and the possibility of using the oil as a source for the compounds production.Aim. Method development for the isolation of thymoquinone as an individual compounds from black caraway (Nigella sativa L.) seed oil, to confirm its structure and determine the degree of purity of the obtained substance.Materials and methods. To confirm the authenticity of the raw materials, analysis of key morphological and anatomical diagnostic features was performed. Quantitative assessment of thymoquinone content in black caraway seeds and control of the isolation process were performed though HPLC analysis. Sample preparation was carried out with methanol by: 1) triple extraction on a boiling water bath; 2) sonification; 3) maceration. The structure of the isolated compound was confirmed through the analysis spectral characteristics using IR spectroscopy by comparing the obtained IR spectrum with the data from the NIST database and one-dimensional NMR spectroscopy.Results and discussion. As a result of the morphological and anatomical analysis, the authenticity of N. sativa seeds was confirmed. Extracts from black caraway seeds obtained by various sample preparation methods were analyzed with HPLC. As a result, it was noted that the method of obtaining the extract does not significantly affect the yield of thymoquinone, the content of which in black caraway seeds is 0.25 ± 0.02 %, which is sufficient for isolation purposes. Through the evaluation of various isolation methods for thymoquinone from black caraway seeds – maceration with alcohol and n-hexane from crushed seeds, liquid-liquid extraction from fatty oil, steam distillation of oil – showed that the best way to obtain thymoquinone is through the distillation of black caraway seed oil with water steam [oil : water ratio (1 : 1)] in a sand bath for 3 hours. The yield of thymoquinone from N. sativa oil is 398 mg from 150 ml of oil (0.26 %). The structure of thymoquinone was confirmed by spectral characteristics in comparison with the NIST database and literature data.Conclusion. The possibility of isolating thymoquinone from Nigella sativa L. seed fatty oil with a chromatographic purity (HPLC) of more than 97 % along with the comparison of the isolated compounds spectral characteristics with literature data, which confirm the identity of the obtained compound, was shown. The proposed express and efficient method for the isolation of thymoquinone through steam distillation provides a yield of the target component of 0.26 %. This method can be applied at roduction sites that harvestand process of black caraway seeds to obtain natural thymoquinone.